Images returned from the RAV: a school that “RE-produces” - Restiglian, Emilia; Da Re, Lorenza (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2019)
The recent introduction of the RAV-Rapporto di autovalutazione in the schools has forced the educational institutions to put on paper some elements that allow to begin for understanding better choices and problems of each school in connection with the reference environment. Starting from data published in the RAVs of all the public secondary schools in Friuli Venezia Giulia and Veneto, our hypothesis was to argument the problem of reproduction of the social structure from the school institutions. This is strictly related with the idea that the national assessment tests are built in the image of an only culture shape, in our case the one spread and reproduced by the “Licei”. Starting from that, we tried to justify the newness of a differentiation of national assessment tests in the secondary school.